To Define the Features of the Course of Secretory Diarrhea in Children And Evaluate the Efficiency of Combined Treatment - Baxodirovich, Tillakobilov Ismoil (European Journal of Life Safety and Stability (2660-9630), 2022)
This article provides information about the study of 56 children aged 12 to 36 months. In the complex therapy of patients, the combined preparation "BioGaia ORS" (oral salt solutions in combination with L. Reuteri Protectis DSM 17938 and zinc salts) BioGaia "BioGaia AB", Sweden) was used in doses according to the instructions for use. Criteria for inclusion in the study: children aged 1 to 3 years, the presence of watery diarrhea with dehydration of I-IIA degrees. The aim of our work was to determine the characteristics of the course of secretory diarrhea in children and evaluate the effectiveness of the combined product "Biogaya ORS". To study the etiology, clinical and laboratory characteristics of watery diarrhea in children using combination therapy containing ORS, lactobacilli and zinc.